Documenting Communism : the Hoover project to microfilm and publish the Soviet archives - Palm, Charles G. (2024)
"A memoir of the project to microfilm and publish ten million pages of Soviet Archives, bringing worldwide access to a Russian history that had been closed for nearly a century